2016
DOI: 10.5604/20831862.1208480
|View full text |Cite
|
Sign up to set email alerts
|

Greater eccentric exercise-induced muscle damage by large versus small range of motion with the same end-point

Abstract: Several factors can affect the magnitude of eccentric exercise (ECC)-induced muscle damage, but little is known regarding the effect of the range of motion (ROM) in ECC-induced muscle damage. The purpose of this study was to investigate whether elbow flexor ECC with 120° of ROM (from 60° of elbow flexion until elbow full extension - 180° [120ROM]) induces a greater magnitude of muscle damage compared with a protocol with 60° of ROM (120-180° of elbow flexion [60ROM]). Twelve healthy young men (age: 22 ± 3.1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This could be explained by the high proportion of monoarticular exercises performed at high intensity over a large range of motion using an isokinetic ergometer. Indeed, it has been shown that exercise intensity [ 35 ] and exercise range of motion [ 36 , 37 ] are dominant factors affecting the magnitude of changes in EIMD markers (e.g. MVC torque loss).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the high proportion of monoarticular exercises performed at high intensity over a large range of motion using an isokinetic ergometer. Indeed, it has been shown that exercise intensity [ 35 ] and exercise range of motion [ 36 , 37 ] are dominant factors affecting the magnitude of changes in EIMD markers (e.g. MVC torque loss).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that the intensity used during the ECC exercise may also affect the muscle damage response [22][23][24][25]. The participants that performed the ECC protocol with a smaller load (25% of MVIC) felt less pain and DOMS than the ECC protocol with greater load (35% of MVIC).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to understand the effects of these variables in isolation on EIMD. Studies in animals [19,20] and humans [15,16,[21][22][23] have consistently demonstrated more severe EIMD when the targeted muscle is stretched over a greater range of muscle lengths. Conversely, when the maximum force output of the muscle is manipulated (i.e., by varying the exercise load or electrostimulation intensity) the impact on EIMD magnitude is less transparent, at least in humans.…”
Section: Introductionmentioning
confidence: 99%